2006
DOI: 10.1029/2005rs003402
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional finite difference time domain modeling of the diurnal and seasonal variations in Schumann resonance parameters

Abstract: [1] The diurnal and seasonal variations of Schumann resonances (SR) have been reported in a number of experiments. In this paper, a three-dimensional FDTD model of the Earth-ionosphere cavity with a day-night asymmetric conductivity profile is employed to study the diurnal and seasonal variability of the power and frequency of the first Schumann resonance (SR) mode. Comparison of the FDTD results and recent experimental measurements shows a clear modulation in the SR power related to the local ionospheric heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…PECHONY AND PRICE: DIURNAL MODULATIONS OF SR dominant role, while the ionosphere height effect appears to have a minor influence on the observed variations in SR field intensities [Large and Wait, 1968;Bliokh et al, 1980;Nickolaenko, 1986;Rabinowicz, 1988;Nickolaenko and Hayakawa, 2002;Yang and Pasko, 2006;Pechony et al, submitted manuscript, 2006].…”
Section: Rs2s05mentioning
confidence: 99%
See 1 more Smart Citation
“…PECHONY AND PRICE: DIURNAL MODULATIONS OF SR dominant role, while the ionosphere height effect appears to have a minor influence on the observed variations in SR field intensities [Large and Wait, 1968;Bliokh et al, 1980;Nickolaenko, 1986;Rabinowicz, 1988;Nickolaenko and Hayakawa, 2002;Yang and Pasko, 2006;Pechony et al, submitted manuscript, 2006].…”
Section: Rs2s05mentioning
confidence: 99%
“…Nevertheless, the source-receiver distance effects are considered to be significant and cannot be completely neglected in favor of the much weaker [Large and Wait, 1968;Bliokh et al, 1980;Nickolaenko, 1986;Rabinowicz, 1988;Nickolaenko and Hayakawa, 2002;Yang and Pasko, 2006;Pechony et al, submitted manuscript, 2006] daynight asymmetry influence. The aim of the present work is to show, using a controlled model experiment, that the local modulation function introduced by SF cannot be associated with variations in the ionosphere height and that SF in fact developed an elegant technique of eliminating the source-receiver distance effect.…”
Section: Introductionmentioning
confidence: 99%
“… Pechony and Price [2004] made theoretical calculations showing that the variability of SR is associated to the distance to the thunderstorm activity area. However in the work of Yang and Pasko [2005, 2006], about the Earth, and previous results using the finite difference time domain (FDTD) technique [ Soriano et al , 2007] on the Mars ionosphere shown that SR frequencies would change under strong variations of the conductivity at altitudes below certain altitude (in Mars 100 km).…”
Section: Introductionmentioning
confidence: 99%
“…Researches on the Schumann resonance parameters (SRs) of the Earth-ionosphere (E-I) system have been reported in many papers [1][2][3] in the recent years. It is believed the properties of SRs (frequencies and quality factors) can reveal physical characteristics of the E-I system such as global temperature, lightning distribution, earthquake phenomena, etc [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed the properties of SRs (frequencies and quality factors) can reveal physical characteristics of the E-I system such as global temperature, lightning distribution, earthquake phenomena, etc [3]. Because accurate SRs variation simulation requires to model the extremely low frequency (ELF) electromagnetic wave propagation and the geology/geodesic information in the whole complex E-I system, it is not until recent years that time-domain numerical algorithms have been applied to such problems [1][2].…”
Section: Introductionmentioning
confidence: 99%